VERY LOW FREQUENCY ELECTROMAGNETIC (VLF-EM) SURVEY FOR GROUNDWATER DEVELOPMENT IN BICHI/BAGWAI AREA, NORTH WESTERN NIGERIA - Mahmud, I.,; Garba, M. L.; Ahmed, I. I.; Onoja, B.; Muhammad, A.; Dahiru, A. T. (FUDMA JOURNAL OF SCIENCES, 2023)
AbstarctDetailed Very Low Frequency Electromagnetic (VLF-EM) hydrogeophysical survey was undertaken to identify conductive zones and recommend potential areas for possible groundwater development in the Bichi area of Kano state northwestern Nigeria. Geologically, the area is characterized by porphyritic granite, coarse grained granite and medium to fine grained granite. The VLF-Electromagnetic method was adopted as a fast reconnaissance tool to map possible linear fractures. During the survey, measurements were taken at a station interval of 20 m along each profile line ranging from 0 – 420 m, making a total of six VLF-EM traverses which were mapped in the study area. The filtered components for both real and imaginary parts of the VLF-EM data were plotted against distance for each profile using the Karous–Hjelt filter® computer software to interpret and identify the top of linear fractures. The Very Low frequency (VLF) normal and filtered component anomalies identified ten (10) major geological interfaces suspected to be faults/fractured zones (f1 – f10). These suspected zones were marked as targets for future groundwater development in the area since these anomalous zones are areas of high conductivity and this parameter is one of the physical characteristics of water saturated zones. Therefore, this work has proven that VLF method is robust in tying down good locations for groundwater development in rural areas.Keywords: Electromagnetic, Hydrogeophysical, Groundwater Development, Conductive Zones, Fault, Fractures.
Keywords: Conductive Zones; Electromagnetic; Fault; Fractures; Groundwater Development; Hydrogeophysical